Jumlah Fibroblas pada Luka Bakar Derajat II pada Tikus dengan Pemberian Gel Ekstrak Etanol Biji Kakao dan Silver Sulfadiazine (The Total Fibroblast on the Second Degree Burns of Rats after Treatment using Ethanolic Extract of Cocoa Beans) - Muhammad Izat Fuadi; Ulfa Elfiah; Misnawi Misnawi (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
The healing process of burns can be disturbed by bacteria and free radicals. Polyphenol (flavonoid and procyanidin) in cocoa have an antibacterial activity, antiinflammatory and antioxidants. This study aimed to investigate the effect of the cocoa beans ethanolic extract on the second degree burns healing process by measuring the number of fibroblasts. The in vivo test was done by creating a second degree burns on the mice backs then treated with either: the ethanolic extract of cocoa beans gel 8 %, Silver Sulfadiazine or Normal saline. The number of fibroblasts was counted in histopatholgy preparations. The result showed the number of fibroblasts 26.67 cells/field of view in Normal saline group; 44.23 cells/field of view in Silver Sulfadiazine group; 50.02 cells/field of view in the ethanolic extract of cocoa beans gel 8 % group. The data analysis showed significant differences between treatment groups. The conclusion was the ethanolic extract of cocoa beans affect the healing process on second degree burns and the number of fibroblasts in the ethanolic extract of cocoa beans gel 8% group was higher than Normal saline and Silver Sulfadiazine groups. Keywords: ethanolic extract of cocoa beans, polyphenols, flavonoids, procyanidin, second degree burns, Silver Sulfadiazine